Professional Practices in Undergraduate Research Programs - Joni M. Seeling (American Society for Microbiology, 2016)
The undergraduate research experience (URE) is an important avenue within a college trajectory in which students enhance their critical thinking, learn about the scientific process, and develop the knowledge and values that will guide their future scientific and professional careers. Individual institutions, programs, departments, and faculty administer undergraduate research differently, but each should adhere to a common set of guidelines which govern the research mentoring process. Adherence to standard practices will enhance the research experience for both students and mentors. This article examines standards and guidelines for professional practices involving undergraduate research and scholarship, and will discuss lapses and limitations that students and faculty frequently confront. The growth, support, and proper management of undergraduate research programs (URPs) at primarily undergraduate institutions (PUIs) is important for maintaining a talented pool of young scientists, as students benefit greatly from direct interactions with faculty mentors that predominate at PUIs.